2018
DOI: 10.1111/odi.12886
|View full text |Cite
|
Sign up to set email alerts
|

Saliva in the “Omics” era: A promising tool in paediatrics

Abstract: In vulnerable populations, such as infants and children, saliva makes the perfect diagnostic medium because of its noninvasive collection, easy handling and storage of samples. Its unique biomarker profiles help tremendously in the diagnosis of many diseases and conditions. In fact, saliva genomics, proteomics, transcriptomics, metabolomics and microbiome-based discoveries have led to complementary and powerful diagnostic information. In children and neonates, saliva is the preferred medium not only for diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 73 publications
1
51
0
4
Order By: Relevance
“…The wide range of saliva biomolecules, including low-molecular-weight compounds (the metabolome), is known to relate to physiological status, thus potentially providing useful data regarding oral and systemic diseases (Pappa, Kousvelari, & Vastardis, 2018;Zhang et al, 2014), while benefitting from non-invasive sampling (Granger et al, 2007). Several metabolomic studies have addressed caries dynamics, using mass spectrometry (MS) or nuclear magnetic resonance (NMR) spectroscopy (Emwas, Salek, Griffin, & Merzaban, 2013;Nascimento, Zaura, Mira, Takahashi, & Ten Cate, 2017).…”
mentioning
confidence: 99%
“…The wide range of saliva biomolecules, including low-molecular-weight compounds (the metabolome), is known to relate to physiological status, thus potentially providing useful data regarding oral and systemic diseases (Pappa, Kousvelari, & Vastardis, 2018;Zhang et al, 2014), while benefitting from non-invasive sampling (Granger et al, 2007). Several metabolomic studies have addressed caries dynamics, using mass spectrometry (MS) or nuclear magnetic resonance (NMR) spectroscopy (Emwas, Salek, Griffin, & Merzaban, 2013;Nascimento, Zaura, Mira, Takahashi, & Ten Cate, 2017).…”
mentioning
confidence: 99%
“…GCF best reflects local periodontal responses since the fluid is derived from the gingival extracellular fluid (Greabu et al, 2009). Fortunately, this quantification has recently been made more efficient by advances in the technologies for detecting small concentrations in low fluid volumes which had been the main challenges in analysing oral GCF (Matczuk et al, 2017; Pappa et al, 2018). Our findings demonstrate that parallel analyses of both fluids give important additional information as also observed in previous studies (Matczuk et al, 2017; Pappa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Both saliva and GCF have been investigated for the measurement of inflammatory processes in the periodontal tissues and were considered superior to serum analysis (Jaedicke, Preshaw, & Taylor, 2016; Taylor & Preshaw, 2016). In addition, saliva has long been proposed as a diagnostic tool with proven effectiveness for investigations of several other systemic conditions (Khaitan, Kabiraj, Bhattacharya, Ginjupally, & Jha, 2015; Lima et al, 2010; Matczuk, Zendzian‐Piotrowska, Maciejczyk, & Kurek, 2017; Pappa, Kousvelari, & Vastardis, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The varnishes used contained 5% sodium uoride, equivalent to 22,600 ppm or 1.19 M of uoride, and calcium phosphate in two chemical forms: CPP-ACP and fTCP. In vitro studies have demonstrated their preventive and remineralizing capacity as they generate supersaturated calcium and phosphate solutions in bio lm and saliva (16) , (24) , (25).…”
Section: Discussionmentioning
confidence: 99%